Case report: Dupilumab-induced linear psoriasis: a rare presentation - Wen Sun; Kexin Wang; Yuekang Ren; Huajie Yuan; Xiaoqing Lang; Shuping Guo; Hongye Liu (Frontiers in Medicine)
A 42 year-old male with prurigo nodularis treated with dupilumab showed a case of linear psoriasis, highlighting the potential of dupilumab to induce immune shift and chimeric gene expression.